Prolonged Successful Cardiopulmonary Resuscitation with Thrombolysis in a Patient with Acute Coronary Syndrome - G. V. Klein; S. E. Chukseev; M. A. Nikolaev; A. A. Timofeev (Рациональная фармакотерапия в кардиологии, 2019)
A case of successful cardiopulmonary resuscitation lasting 120 min with a good neurological outcome in a patient with acute coronary syndrome is presented. The protocol of resuscitation with the use of thrombolysis (recombinant non-immunogenic staphylokinase) followed by stenting of the infarct-dependent artery in a patient with acute coronary syndrome is described on the example of this case.